Sustainable Logistics: Green Solutions, Technologies and Challenges in the Service of Industrial Efficiency - Szentesi, Szabolcs; Nagy, Gábor; Kiss-Simon, Dániel (Advanced Logistic Systems - Theory and Practice, 2025)
This study explores the development opportunities of sustainable logistics systems, with a particular focus on environmentally friendly technologies and green solutions that enhance industrial efficiency. It provides a detailed overview of innovative technologies applicable in transportation and supply chain processes, emphasizing their impact on energy efficiency, cost optimization, and environmental load reduction. The analysis covers key Industry 4.0 tools, including the integration of IoT and artificial intelligence into logistics, as well as the applicability of alternative fuels and emission reduction strategies. The aim of the study is to formulate strategic guidelines and practical recommendations for integrating sustainability at all levels of logistics systems, thereby promoting both environmentally and economically efficient operations.